Simulation-based performance of transport protocols using MPEG-4 traffics over 4G network - Kamil, Wisam Abduladheem; Alubady, Raaid; Awang Nor, Shahrudin (2015)
Abstract- Four Generation (4G) networks are the boiling connection over the airwaves since it can support the far geographic distance over the world, especially are to the popularity of the wireless devices.The Long-Term Evolution (LTE) is often called the 4G. Nowadays, telecommunications, video traffic has burgeoned under the development of LTE, the truly underlying access technology of 4G networks.During LTE deployment, different transport protocols are the most recommended and widely studied such as Transmission Control Protocol (TCP), User Datagram Protocol (UDP) and Datagram Congestion Control Protocol (DCCP), which can perform differently on 4G networks depends on the network's scenario as well as parameters setting. Although the LTE deployment is rapidly apace, there is a lack of performance evaluation of its protocols.Therefore, an extensive analysis is needed to evaluate the performance of various protocols for high end applications like multimedia applications. Supporting these multimedia applications with varied quality of service (QoS) requirements while maximizing the resource utilization is a challenging task. To achieve the objective of this study, this work tries to answer the following questions: are the old protocol suit with this new technology; which one has the best performance and; which one has the greatest effect on throughput, delay, packet loss. In this study, our analysis and compare are on the performance of different the Internet transport protocols for streaming video via using the simulation environment. Through the Network Simulation-3 (NS3), the performance of transporting an MPEG- 4 video stream, including throughput, delay, and packet loss are analyzed at the base station through TCP, UDP, and DCCP protocols over 4G-LTE technology.The results show that DCCP has a better throughput, and a lesser delay, but at the same time it has more packet losses than UDP and TCP.Based on the results, DCCP is recommended as a transport protocol for realtime video.